The Influence of Green Brands on Eco-Labeling and Eco-Branding on Green Purchase Intention in Skincare Products - Zima Khalifatul Aulia; Ihwan Susila (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine theleffect of greenlbrands on consumerlpreferences in thelcontext of thelfacial carelindustry. At this time, there is a trend in skincare, so many companies compete to provide the best service for their consumers, but many of these companies do not pay attention to the condition of the surrounding environment. Even though a lot of skincare waste threatens the environment because it is not managed properly by the company that produces the skincare. Around us, there are only a few companies that pay attention to the composition of the products used by the company, then the product is not tested on animals such as rabbits and uses packaging that is easily recycled or can even be easily decomposed in the soil. This is done toltest the effectlof greenlbrands on greenlpurchaselintentionlby considering eco-brandinglandleco-labeling. Because green brandlrefers to algreen brand or product that commits to thelenvironment, eco branding is also a link between consumer perceptions of greenlbrand and green purchaselintention. This studyluses alquestionnaire and purposivelsampling method tolcollect data fromlrespondents, which requires approximately 185 data and will then be processed using a data processing application, Smart Pls. So, the empirical resultslof the study stating that the “Green Brand Effect” can significantly mediate between “Eco Branding” and “Eco Labeling” indicate that when a brand has a strong eco-branding strategy, it can increase consumers' perception of the brand as environmentally friendly and can affect customer purchase intentions. Then things that can be done by the NPure skincare company by having a long-term continued commitment and also a clear goal to reduce the impact of the bad environment and provide good NPure product innovations to make a good contribution to the environment.